Prediction of long-term major adverse cardiac events after myocardial infarction: value of combination of inflammatory biomarkers and GRACE score - Tian, Dan; Yu, Nianxi; Mao, Tianxiao; Li, Yanli; Liu, Ruiyan; Xu, Ye; Huang, Dong; Lv, Qianzhou; Pan, Kunming (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThis study aims to investigate the prognostic value of integrating inflammatory biomarkers with the established Global Registry of Acute Coronary Events (GRACE) risk score for predicting clinical outcomes in patients with myocardial infarction (MI).MethodsThis prospective, single-center study enrolled adult MI patients admitted to the coronary care unit at Zhongshan Hospital, Fudan University. Blood samples were collected to measure inflammatory markers (IL-1β, sIL-2R, IL-6, IL-8) and myocardial biomarkers. The Gensini score and GRACE score were calculated for each patient. The primary endpoint was the post-MI occurrence of a composite of major adverse cardiovascular events (MACE), including cardiovascular death, non-fatal MI, and non-fatal ischemic stroke. Predictive performance of biomarkers was evaluated using Kaplan–Meier survival curves, Cox regression analysis, and receiver operating characteristic (ROC) curves.ResultsA total of 724 patients (median age 64 years, 85.0% male) were included with a median follow-up of 1.7 years. During follow-up, 81 patients (11.1%) experienced MACE, including 45 cardiovascular deaths, 23 MIs, and 13 strokes. Multivariate Cox regression analysis revealed that sIL-2R and IL-8 were independent predictors of MACE. Elevated levels of sIL-2R (HR = 9.123, 95% CI: 5.883–14.147, p < 0.001) and IL-8 (HR = 4.443, 95% CI: 2.769–7.131, p < 0.001) were significantly associated with an increased risk of MACE. After adjustment for cardiovascular risk factors, elevated sIL-2R (adjusted HR: 3.761, 95% CI: 2.269–6.233, p < 0.001) and IL-8 (adjusted HR: 2.294, 95% CI: 1.375–3.825, p = 0.001) levels remained significantly associated with an increased risk of MACE. The combination of sIL-2R, IL-8, and GRACE score displayed effective predictive performance for long-term MACE, as evidenced by ROC curve analysis (AUC = 0.824, 95% CI: 0.775–0.873, p < 0.001).ConclusionElevated levels of sIL-2R and IL-8 independently predict increased risk of MACE in MI patients. Integrating biomarkers such as sIL-2R and IL-8 with the GRACE score can significantly improve predictive performance, offering a robust approach for risk stratification in MI patients.